A linguagem cartográfica no ensino e aprendizagem de geografia para alunos cegos - Tibola, Maiara (2016)
This essay was developed in the perspective to think in quality of the teaching and learning of Geography for blinds in Francisco Beltrão-PR. For this propose, from the reality of schools, the necessity of building of tactile educational materials that allow the orientation. The search has three specific objectives: to identify how is the teacher's mediation in the process of the teaching and learning of Geography for blinds; To understand how is the spatial location of the geographical phenomenon represented in map; to establish the articulation between matter and form, by means of cartographic language, for that geographical term be built, with approach for the inclusive perspective in Brazil and the progress according with the laws. The search has the hypothesis that there is the necessity to form one context more accurate of situation of education theses subjects, just as well, in necessity for change in form of to teach in mainstream education schools. The theoretical approach was guided in Vygotsky that investigated the process of school inclusion, just as well in teaching and learning of Geography. To realize the search we identify the educations institutions that has blind students in mainstream education in Francisco Beltrão-PR, and theses, we assess the questionnaire answered by Geography teachers of mainstream education with blind students. In sequence, we interview the teachers that realize the Atendimento Educacional Especializado (AEE) (Special Education Services, SES), do Centro de Atendimento Especializado ao Deficiente Visual (CAEDV) (Accessibility Center to the Visually Impaired Student), also was analyzed the Centro de Apoio Pedagógico para Atendimento às Pessoas com Deficiência Visual (CAP) that provide adapted materials for the teaching and learning of students and the Geography's teacher in public school. We identify one case of blind student that attended in 8ºgrade of elementary school. The interviews had for objective to identify how the inclusion of blind students in schools, to analyze the materials conditions of work of teacher, and to refer the difficult of teacher about the teaching of Geography for blind students. The activities with maps mediate the process of investigation how the blind student understands geographical area by means of route: house until the school, front of school until the classroom; in classroom and house until downtown Francisco Beltrão. From now, education materials were building to mediate the understanding of location of student, since the Geography is built from of events off classroom. This way, the results of search were the limitations of blind students, as absence of vision, can be overcome, provided realize the process of interaction of subjects with social environment, to have domain of cartography language and with the use of tactile educational materials.